Labour relations in comparative perspective: Special focus on the SME sector - Csaba Makó; Péter Csizmadia; Miklós Illéssy (Journal for East European Management Studies, 2006)
The evolution of the view and practice of social partnership is one basic element in the construction of the European Union. The paper gives an overview on the key actors and institutions of Labour Relations System (LRS) with special focus on the micro- small and medium sized enteprises (SME). In the first section, the author describes the key social partners and institutions of the LRS in the countries participating in an international research project carried out in 2003-2006 and supported by the Leonardo Programme of the EU (Annex 1). The second section of the paper deals with the particular features of the LRS in the SME sector. The strong informality of social dialogue is the key institutional pattern of LRS in the SME sector. – – Die Evolution der Ansicht und Anwendung von sozialen Partnerschaften ist ein Basiselement in der Konstruktion der Europäischen Union. Der Aufsatz gibt einen Überblick über die Hauptakteure und Institutionen des Labour Relations System (LRS), mit dem Augenmerk auf kleine und mittelgrosse Unternehmen (SME). Im ersten Abschnitt beschreibt der Autor die wichtigen sozialen Partner und Institutionen der LRS in den beteiligten Ländern an einem internationalen Forschungsprojekt in 2003-2006, unterstützt vom Leonardo Programm der EU (Annex 1). Der zweite Teil behandelt die spezifischen Eigenschaften des LRS im SME Sektor. Die ausgeprägte Informalität des sozialen Dialogs ist ein wichtiges institutionelles Muster der LRS im SME Sektor.
Keywords: 650; Labour Relations System; Social Actors and Institutions; Collective Bargaining; Works Council; Informal Regulation; SME